Management of services in total quality management implemented and non-implemented health facilities - Begum, Muhsina; Saha, Ashees Kumar; Begum, Sheuly; Akhter, Nasima; Borua, Pritikona; Riaz, Baizid Khoorshid (Asian Journal of Medical and Biological Research, 2021)
5S-CQI-TQM is a management technique that is aimed at bringing satisfaction of staff as well as the patients through improvement of working environment. A cross-sectional comparative study was carried out among 226 respondents who were selected purposively from the selected study place from 1st January to 31st December 2017. Among 226 respondents, 113 were taken from Dhaka Medical College and another 113 were taken from Mugdha Medical College. Among 113 respondents, 56 respondents were health care providers and 57 respondents were health care receivers. The purpose of this study to compare the management of services in Total Quality Management implemented (Dhaka Medical College and Hospital) and non-implemented (Mugdha Medical College and Hospital) health facilities. A Semi-structured interviewer administered questionnaire and an observational check list were developed to collect the data. Separate questionnaire was used for health care providers and health care receivers. The statistical analysis was conducted using SPSS (statistical package for social science) version 20 statistical software. Significant statistical differences were found between TQM implemented and TQM non-implemented hospital regarding workload (p=0.043), hospital authority always seriously consider staff’s suggestions for the improvement of quality of service (p<0.001), employees always respect to each other in the hospital (p<0.001) and 35 (62.5%) service providers expressed satisfactory opinion regarding management of the hospital. Asian J. Med. Biol. Res. December 2020, 6(4): 689-696